Saponin adjuvant primes for a dominant interleukin-10 production to ovalbumin and to Trypanosoma cruzi antigen. - Tadokoro, C E (1996)
The adjuvant activity of saponin for T-cell responses was evaluated and compared with that of complete Freund's adjuvant (CFA) in two antigen systems: a lysate of the protozoa Trypanosoma cruzi and ovalbumin (OA). Strong delayed-type hypersensitivity and T-cell proliferate responses, comparable with those stimulated by CFA, were observed for both antigens following immunization with saponin as adjuvant. Upon in vitro secondary antigen stimulation, high interleukin-10 (IL-10) and low interferon-gamma (IFN-gamma) levels were observed in lymph node (LN) cell cultures from saponin-immunized mice in contrast with the high IFN-gamma and decreased IL-10 production by LN cells from CFA-immunized mice. Production of IL-10 and IFN-gamma in these conditions was CD4-activation dependent. Concanavalin A (Con A)-stimulated interleukin-4 (IL-4) production was higher in saponin-immunized mice than in CFA-immunized mice. IL-10 produced by LN cells from saponin-immunized mice suppressed IFN-gamma production and Con A-induced proliferation. Taken together, these data are consistent with in vivo stimulation of both T-helper (Th)1 and Th2-type cells by immunization with saponin; in vitro a Th2-type cytokine response with high IL-10 production predominates, indicating preferential priming towards a Th2-type response. Immunization with CFA induced a Th1-type cytokine response. To our knowledge this is the first report in which an adjuvant is shown to prime for a dominant IL-10 production.